Ethnic reasoning and early Christian identity: A Pauline theological perspective - Toit, Philip La Grange Du (HTS teologiese studies, 2020)
Within the ethnic-reasoning position, which has gained momentum in recent years, it is argued that in the in-Christ identity there exists no dichotomy between natural, physical relationships and constructed, made-up relationships. Ethnicity is viewed as fluid and changeable and as including the category of religion, which is understood as involving a nation’s culture and their cultic and ritualistic practices. Yet, it is a question whether these notions are compatible with the way in which the in-Christ identity is portrayed, especially by Paul. In terms of the theological way in which ethnicity and even religious practices are portrayed, they rather belong to the domain of humanness or human conduct, and thus to the anthropological domain. In contrast, believers’ relation to Abraham and their new mode of identity in the S/spirit is portrayed as being in contrast with the anthropological domain or the domain of ‘flesh’, which includes things such as ethnicity, human conduct and even religious practices. This tension between divine identity and human or natural identity in the New Testament is accounted for and applied to the ethnic-reasoning position, which also influences the way in which the in-Christ identity finds cultural expression in the lives of present-day readers.